Pelaksanaan Asesmen Risiko Jatuh di Rumah Sakit - Hirza Ainin Nur; Edi Dharmana; Agus Santoso (Alma Ata University Press, 2017)
Falls are the most worrying incidence of patients in the hospital and that has an impact on injury and even death. The incidence was second ranks of adverse event after medication errors. Hospitals are already making efforts to reduce the fall incident but in reality, the incidence of falls still occurs. Data obtained from March to September 2016 have 6 cases of incident patients falling from a total of 43 patient safety incidents. The results of the observations show that most of the fall prevention programs that have not been done are falling risk assessments. Fall risk assessment is the first step to prevent the occurrence of falls in the patient, if not done then the incident will occur. This study aims to explore the implementation of falls risk assessment conducted by nurses in the hospital wards. The research method using qualitative research with phenomenology approach. The population used is inpatient ward nurses as many as 304 nurses.The sample used by purposive sampling technique with 10 informants. Data collection using primary and secondary data. Primary data obtained by in-depth interview with semi-structured interview to all informants. Secondary data was used document review of SOP prevention of fall risk, assessment protocol, and patient's medical record status. Data analysis used Miles and Huberman analysis model by reducing data, making display data, and drawing conclusions. The results of the research are two themes that are the existence of internal training and socialization affects the nurse's understanding of the implementation of falls risk assessment both initial of falls risk assessment and re-assessment of falls risk and implementation of falls risk assessment influenced by the inhibiting and supporting factors, both of these factors affect compliance of falls risk assessment conducted by the nurse. This study suggests that the understanding of fall risk assessment does not guarantee the nurse to always adhere to the implementation of fall risk assessment. It is expected that there will be cooperation between hospital management, working group prevention of falls risk, and head of ward to always supervise and monitor evaluation related to implementation of falls risk assessment along with giving reward and punishment.